Ethical dilemmas of the handicapped’s cultural narrative - França, Inacia Sátiro Xavier de; Vieira, Neiva Francenelly Cunha; Barroso, Maria Grasiela Teixeira; Varela, Zulene Maria de Vasconcelos (Rev Rene, 2004)
This is a reflexive study focused on the ethical dilemmas of the researcher-informer interaction in the context of ethnography on the handicapped. This reflection cites the steps of ethnographic research, mentions the determinant factors of ethical dilemmas in the context of cultural narratives and suggests procedures so that the ethnographer’s personal identity should not be influenced by any alteration of the researcher-informer binomial. It is possible to conclude that ethnography favors the emergence of interactive conflicts related to the perception of the “myself-someone else” binomial, establishing the idea of alteration, prejudice, and the possibility of the emergence of ethical dilemmas. Because of this, the interpretative position of a researcher needs to accept differences and respect the dignity of the human being.